Реґіональний зріз Української революції 1917–1921 рр.: Миколаївщина - Котляр, Ю.; Левченко, Л. (Український історичний журнал, 2019)
На прикладі Миколаївщини висвітлюються особливості Української революції 1917–1921 рр. на реґіональному рівні. Автори використали
методи: порівняльно-історичний, що дав змогу зіставити події Української
революції на всеукраїнському та реґіональному рівнях; хронологічний – допоміг
установити відмінності між датуванням подій у Києві та Миколаєві; логічний – надав можливість об’єднати та узагальнити вже виявлені історичні факти й визначити особливості революційних подій на Миколаївщині. Наукова новизна дослідження полягає в тому, що вперше на основі неопублікованих
джерел та наявної історіографічної бази визначено специфіку подій Української
революції 1917–1921 рр. на території Миколаївщини. Головні революційні події
тут відбувалися в контексті державотворчих процесів в Україні (періоди Центральної Ради, гетьманату, Директорії). На місцевому рівні часто ці періоди хронологічно не збігаються із загальною періодизацією Української революції.
Наприклад, на Миколаївщині період Центральної Ради розпочався пізніше, а
саме після Жовтневого перевороту в Петрограді; період Директорії закінчився
значно раніше, від другого захоплення влади більшовиками. Чіткий орієнтир на
Українську Центральну Раду Миколаївщина взяла після приходу до влади більшовиків у Петрограді. Визнання УЦР у реґіоні відбулося завдяки наполегливості Миколаївської ради об’єднаних українських організацій. Центральна Рада не
мала чітко окресленої реґіональної політики, що врешті призвело до втрати
нею авторитету серед селян і містян. Натомість місцеві більшовики, які на
початку революції фактично були марґінальною політичною силою, зміцнилися й набули авторитету. Уряд П.Скоропадського, намагаючись виправити помилки Центральної Ради, приділив значну увагу миколаївським суднобудівним
заводам, домігся повернення Україні флоту й верфей. Проте через німецьку політику щодо підприємств, а також з огляду на короткочасність перебування при владі значних результатів у цій сфері також не здобув. Тримісячний період
Директорії відзначився хаотичністю влади й подій, в яких важливу роль відіграла присутність військ Антанти та переміна політичних поглядів отамана Н.Григор’єва – з проукраїнських на більшовицькі. Саме дії григор’євців призвели
до остаточної втрати впливу Миколаївської ради об’єднаних українських організацій на офіційну владу. Важливу роль відігравав селянський повстанський рух, який тривав і після завершення основних революційних подій. Using the example of Mykolaiv region the authors highlight the features of the Ukrainian
Revolution of 1917–1921 at the regional level. A comparative-historical method made
it possible to compare the events of the Ukrainian Revolution at the national and
regional levels; chronological method helped to establish difference between dating of
the events in Kyiv and Mykolaiv; logical method provided an opportunity to combine
and summarize historical facts which had already revealed earlier, and identify the
features of the revolutionary events in Mykolaiv region. The scientific novelty of this
study is that for the first time the specificity of the events of the Ukrainian Revolution
of 1917–1921 on the territory of the Mykolaiv region was discovered on the basis of
unpublished sources and available historiographic basis. The main revolutionary
events in the Mykolaiv region occurred in the context of state-building processes in
Ukraine (periods of the Central Rada, P.Skoropadskyi and the Directory). At the local
level, often these periods do not coincide chronologically with the general periodization
of the history of the Ukrainian Revolution. For example, in Mykolaiv region the period
of the Central Rada began later, namely after the October 1917 coup in Petrograd; the
Directory period ended much sooner, after the second seizure of power by the Bolsheviks.
A strong signal to the Ukrainian Central Rada was taken by the Mykolaiv Region after
the Bolshevik coup in Petrograd. The recognition of the Ukrainian Central Rada in
the region was due to the persistence of the Mykolaiv Council of United Ukrainian
Organizations. The Central Rada did not have a clearly defined regional policy. This
resulted in the loss of its credibility among peasants and townspeople. In the Mykolaiv
area the Central Rada made mistakes in the land policy and did not take into account
the powerful city factor – workers of the Mykolaiv shipyards. The peasants and the
townspeople did not solve their major problems. This led to uprisings both in the city and
in the countryside. The belated attention of the Central Rada to the events in Mykolaiv
had no positive consequences. Instead, the local Bolsheviks, who at the beginning of the
revolution were in fact a marginal political group, strengthened and gained influence
among the proletarians and peasants of Mykolaiv region. Trying to correct the errors
of the Central Rada the government of P.Skoropadskyi paid considerable attention to
the Mykolaiv shipyards, achieved the return of Ukraine’s fleet and shipyards. However,
due to the German policy towards the shipyards and encroachment on unfinished
warships, as well as the short term of power, it also failed to achieve significant results
in this sphere. With it, in the period of P.Skoropadskyi the confrontation deepened
between peasants and large landowners, which resulted in anti-hetman movement and
uprisings. In the city, Ukrainian organizations under the Hetmanate did not have a
significant impact on the population and official authorities because of ignoring them
by German command and appointing former Russian generals to senior positions.
The three-month period of the Directory is characterized by the chaotic power and
events in which the presence of the Entente troops and the change of political views of
Ataman N.Hryhoriev – from pro-Ukrainian to Bolshevik ones – played an important
role. It was Hryhoriev’s actions that led to the final loss of influence of the Mykolaiv
Council of United Ukrainian Organizations on official authorities. Although First
Winter Campaign of the Army of UPR covered a large part of the territory of Mykolaiv region and became a heroic page in the history of the Ukrainian Army, it had no natural connection with the processes taking place in Mykolaiv region. Instead, the
peasant rebel movement played an important role and continued even after the major revolutionary events had ended.